Comparison of Control Strategies for AC-DC Converter for a Wind Energy System with Permanent Magnet Synchronous Generator. - Gallo Tibanquiza, Alberto Enrique (2023)
Wind energy contributes to diversifying the energy matrix. These systems can be adapted to various scales, from industrial wind farms to smaller residential systems, makingaccessible and versatile. Furthermore, wind systems promotes environmental preservation by reducing dependence on nonrenewable energy sources like fossil fuels, significantly contributing to climate change mitigation. The challenge posed by wind energy lies in controlling it against disturbances with high variability, such as wind speed. To address this challenge, advanced control systems must be implemented to optimize the performance of wind turbines and minimize the adverse effects of varying wind conditions. This work presents the design and implementation of two control strategies for the AC/DC converter of a wind system with a PMSG generator. First a traditional PI controller is used, followed by a PI+Fuzzy-PI controller. The aim is to analyze and compare the dynamic performance of both control techniques. The results show that the PI+Zuzzy-PI controller has a better dynamic performance than PI controller. The overshoot and settling time can be reduced in the former. Therefore, the effectiveness of PI+Fuzzy - PI controller is evaluated and demonstraed.